Chalcogenide and pnictide nanocrystals from the silylative deoxygenation of metal oxides. Issue 38 (19th September 2017) - Lin, Chia-Cheng; Tan, Shannon J.; Vela, Javier
Abstract : Transition metal chalcogenides and pnictides are interesting in optoelectronics and catalysis. We present a generalized method to transform preformed metal oxide nanocrystals into sulfides, selenides, or phosphides via silylative deoxygenation with trimethylsilyl reagents. In all reactions studied, simultaneous decomposition of excess silyl reagent produces a protective, amorphous silica coating around the newly formed nanocrystals. Abstract : Transition metal chalcogenide and pnictide nanocrystals are of interest for optoelectronic and catalytic applications. Here, we present a generalized route to the synthesis of these materials from the silylative deoxygenation of metal oxides with trimethylsilyl reagents. Specific nanophases produced in this way include Ni3 S2, Ni5 Se5, Ni2 P, Co9 S8, Co3 Se4, CoP, Co2 P, and heterobimetallic (Ni/Co)9 S8 . The resulting chalcogenide nanocrystals are hollow, likely due to differential rates of ion diffusion during the interfacial phase transformation reaction (Kirkendall-type effect). In contrast, the phosphide nanocrystals are solid, likely because they form at higher reaction temperatures. In all cases, simultaneous partial decomposition of the deoxygenating silyl reagent produces a coating of amorphous silica around the newly formed nanocrystals, which could impact their stability and recyclability.